Densely calcified tuberculous constrictive pericarditis with concurrent active pulmonary tuberculosis infection - Laudari, S; Dhungel, S; Gautam, S; Dubey, L; Prasad, G; Bhattacharya, R; Subramanyam, G (Journal of College of Medical Sciences-Nepal, 2015)
Though pulmonary tuberculosis is a common chronic infection in the developing countries like Nepal, the incidence of tubercular constrictive pericarditis is very low. Here we report a patient of active pulmonary tuberculosis with sputum positive for acid fast bacilli along with densely calcified constrictive pericarditis which has been reported as a very rare presentation in the literature. DOI: http://dx.doi.org/10.3126/jcmsn.v10i2.12955 Journal of College of Medical Sciences-Nepal, 2014, Vol.10(2); 41-43